6th extinction : a Sigma Force novel - Rollins, James, 1961- (Rollins, James, 1961- Sigma Force novel, 2014)
A remote military research station in Utah sends out a frantic distress call, ending with a chilling final command: Kill us all! Personnel from the neighbouring base rush in to discover everyone already dead - and not just the scientists, but every living thing for fifty square miles has been annihilated. The land is entirely sterile-and the blight is spreading. To halt the inevitable, Commander Gray Pierce and Sigma must unravel a threat that rises out of the distant past, to a time when Antarctica was green and all life on Earth balanced upon the blade of a knife. Following clues from an ancient map rescued from the lost Library of Alexandria, Sigma will discover the truth about an ancient continent, about a new form of death buried under miles of ice.